Pemahaman Ayat-Ayat Tazkiyatun Nafs dan Korelasinya dengan Praktik Tawajjuh dalam Tarekat Naqsyabandiyah Tanah Merah Kabupaten Aceh singkil - Pahmi Rijal Solin; Muhammad Hidayat; Fadhilah Is (Program Magister Ilmu Al-Qur'an dan Tafsir, Fakultas Ushuluddin dan Pemikiran Islam, Universitas Islam Negeri Raden Fatah Palembang, 2024)
This research aims to find out how the understanding of Tazkiyatun Nafs verses according to Tarekat Naqsyabandiyah Tanah Merah and how it relates to the practice of Tawajjuh activities in this tarekat. This research uses qualitative methods with the type of field research as many as three informants. In collecting data, the methods used are observation, interview and documentation. The results showed that the Tarekat Naqsyabandiyah reached Aceh Singkil, especially in Tanah Merah, brought by Shaykh H. Bahauddin Tawar. Kitab Tafsir Jalalain is a reference book used in this order in interpreting the verses of the Qur'an. Tazkiyatun Nafs verses such as in QS. ash-Syam verses 9-10 and QS. ar-Ra'd verse 28 are used as a guide to achieve purity of soul and peace of heart through dhikr. The practice of Tawajjuh in this tariqah involves dhikr and direct spiritual guidance from the teach teacher to the student, with the aim of strengthening the relationship with Allah SWT and to purify the soul from bad traits.